IMPLEMENTASI TEORI KARIR DONALD SUPER PADA KARIR YOUTUBER DAN PEGIAT MEDIA DI ERA MILENIAL (STUDI KASUS MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS HAMZANWADI) - Aulia, Fitri; Yulianti, Dewi (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Career choices in the millennial era have patterns that are identical to the world of technology, such as content creators, YouTubers, media activists and gamers. The guidance and counseling profession is also not a barrier for students to pursue careers in the world of technology. Based on the findings, there are two students who are pursuing careers such as YouTubers and media activists with 55.7 million subscribers and hundreds of media and video works. This research uses case study method. Data was collected by means of interviews, observation, documentation studies. Based on the results of the study, it was found that (1) these two students became YouTubers and media activists according to their potential, interests and talents. This is what is meant by the positive Self concept meant by Donald Super. Where the positive self-concept seems to be the driving force to form career patterns throughout their lives. This is manifested in totality in every work produced. (2) these two students are in the exploratory stage (15-25 years). Where they have been able to understand a profession with an interest in the talent they have. Although there is potential to develop in other directions. Keywords: youtuber, media activist, Donald Super’s Career Theory